Asas Keseimbangan dalam Perancangan Kontrak Antara Pemberi dan Penerima Waralaba di Indonesia - Ni Putu Novia Erlina Putri; Made Aditya Pramana Putra (CV. ITTC INDONESIA, 2026)
This article examines the application of the principle of balance in the formulation of franchise agreements in Indonesia using a normative legal research method with a qualitative approach, including statutory, conceptual, and analytical perspectives. The study explores the legal framework consisting of the Indonesian Civil Code (KUH Perdata), Government Regulation No. 42 of 2007 on Franchising, and Minister of Trade Regulation No. 71 of 2019 on Franchise Implementation. It also identifies the sources of imbalance between franchisors and franchisees in contractual practices. The findings reveal that the dominance of standard-form contracts and unequal bargaining positions often result in clauses that disproportionately favor franchisors. Meanwhile, the existing regulations emphasize administrative compliance and procedural transparency rather than ensuring substantive fairness within contractual terms. This condition allows the continuation of exploitative practices, even when formal requirements are fulfilled. To address these issues, this study recommends strengthening administrative authority to review contract fairness, implementing a key fact sheet for prospective franchisees, developing balanced model clauses, and promoting accessible dispute resolution mechanisms. These measures are expected to reinforce the principles of balance and good faith, creating a fair, ethical, and sustainable franchise system in Indonesia.